Targeting Multidrug-resistant Staphylococci with an anti-rpoA Peptide Nucleic Acid Conjugated to the HIV-1 TAT Cell Penetrating Peptide - Mostafa FN Abushahba; Haroon Mohammad; Mohamed N Seleem (Elsevier, 2016)
Staphylococcus aureus infections present a serious challenge to healthcare practitioners due to the emergence of resistance to numerous conventional antibiotics. Due to their unique mode of action, peptide nucleic acids are novel alternatives to traditional antibiotics to tackle the issue of bacterial multidrug resistance. In this study, we designed a peptide nucleic acid covalently conjugated to the HIV-TAT cell penetrating peptide (GRKKKRRQRRRYK) in order to target the RNA polymerase α subunit gene (rpoA) required for bacterial genes transcription. We explored the antimicrobial activity of the anti-rpoA construct (peptide nucleic acid-TAT) against methicillin-resistant S. aureus, vancomycin-intermediate S. aureus, vancomycin-resistant S. aureus, linezolid-resistant S. aureus, and methicillin-resistant S. epidermidis in pure culture, infected mammalian cell culture, and in an in vivo Caenorhabditis elegans infection model. The anti-rpoA construct led to a concentration-dependent inhibition of bacterial growth (at micromolar concentrations) in vitro and in both infected cell culture and in vivo in C. elegans. Moreover, rpoA gene silencing resulted in suppression of its message as well as reduced expression of two important methicillin-resistant S. aureus USA300 toxins (α-hemolysin and Panton-Valentine leukocidin). This study confirms that rpoA gene is a potential target for development of novel antisense therapeutics to treat infections caused by methicillin-resistant S. aureus.